The validation and application of Inertial Measurement Units to springboard diving. Issue 4 (2nd October 2017) - Walker, Cherie; Sinclair, Peter; Graham, Kenneth; Cobley, Stephen
Abstract: Inertial Measurement Units (IMUs) may offer an ecologically valid, reliable, and practical method for biomechanical performance analysis. With such potential in mind, Part 1 of this study examined the accuracy of IMUs gyroscopes with an optical system (Cortex 3.3). A calibration formula standardised the IMUs angular velocity output with the optical system. The percentage differences between the two measures = 0.5% ( p  < 0.05), suggest IMU's efficacy for application. In Part 2, the aim was to examine and understand how dive flight angular velocity time series plots change and increase according to dive degree of difficulty. With IMUs attached to three competitive divers performing forward somersault dives, dive flight kinematics were assessed. Biomechanically, a 4½ tuck somersault dive differed to lower degree of difficulty dives in terms of: (1) a rotational delay immediately after takeoff (to gain greater vertical translation); (2) increased total time of flight; (3) greater muscle effort to resist increased centrifugal forces produced by the increased angular velocity (1, 090 °/s); and (4) greater eccentric control during deceleration allow a safe and vertical entry into the water. IMUs can be effectively utilised and integrated into contexts such as springboard diving for performance analysis and optimisation purposes.